InDesign; CS2 For Dummies. - Galen Gruman (Wiley, 2005)
Over the last few years, Adobe InDesign has made significant inroads against QuarkXPress, with adoptions by major media companies such as Meredith Corporation and Hearst Magazines; it is now the only desktop publishing program taught at many art schoolsShows graphic designers how to get up to speed quickly on the latest InDesign release, make the most of program tools, create great page designs, add sparkle, and output to a variety of mediaThe authors, both Quark experts who've converted to InDesign, offer special tips and insights to Quark users who are making (or thinking of.